Laparotomi Eksplorasi, Drainase Asites, Drainase Abdomen, dan Appendektomi atas Indikasi Abses Intraabdomen, Asites Masif dengan Apendisitis - Rajiv Andika Mustafa; Maurits Tamalonggehe; Astri Avianti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
ABSTRACT Acute appendicitis is one of the most common abdominal surgical emergencies. Delayed diagnosis and management can lead to serious complications such as appendiceal perforation, generalized peritonitis, intra-abdominal abscesses, sepsis, and organ dysfunction. Massive ascites accompanying complicated appendicitis is a rare condition that indicates severe intra-abdominal inflammation, requiring a comprehensive diagnostic and therapeutic approach and immediate surgical intervention. We report a case of a 56-year-old man who presented to the emergency department with complaints of right lower abdominal pain that had worsened several days prior to admission, accompanied by fever, nausea, vomiting, abdominal distension, and inability to pass flatus. Physical examination revealed signs of generalized peritonitis and massive ascites. Laboratory tests revealed severe leukocytosis, anemia, hyponatremia, metabolic acidosis, and renal dysfunction leading to sepsis-associated acute kidney injury. The patient was diagnosed with complicated acute appendicitis with intra-abdominal abscess and massive ascites. The patient underwent exploratory laparotomy, ascites drainage, abdominal drainage, and appendectomy. Postoperatively, the patient's clinical condition and laboratory parameters showed significant improvement. Complicated acute appendicitis with intra-abdominal abscess and massive ascites is a life-threatening condition that requires prompt and accurate diagnosis and surgical intervention. Exploratory laparotomy accompanied by control of the source of infection and adequate supportive therapy provided favorable clinical results. Comprehensive management plays an important role in reducing morbidity and improving patient prognosis. Keywords: Appendicitis, Intra-Abdominal Abscess, Massive Ascites, Exploratory Laparotomy, Appendectomy